Does Monetary Policy Work Effectively In 10 European Countries? New Evidence From Fisher Effect - Ling, Tai-Hu; Liew, Venus Khim-Sen (2013)
This study examines the Fisher effect for 10 European Union countries over a period from January 1987 to December 2012. A battery of panel unit root tests shows that the monthly real interest rates in these countries are mean reverting. The series-specific panel SURADF test of Breuer et al. (2002) reveals that 9 country series reject the unit root null hypothesis, except for 1 country series. These results have one extremely important policy implication is that monetary collaboration within 10 European counties is the key determinant to achieve the long-run macroeconomic stability. Policy makers in European Central Bank need to closely monitor the monetary stability particularly in Luxembourg towards establishing a strong European monetary union.